DEVELOPMENT OF SMP PGRI REJOTANGAN WEBSITE USING THE PERSONAL EXTREME PROGRAMMING MODEL - Ilham Dwiki Arifani; Vertika Panggayuh; Farid Sukmana; Umi Chotijah (STKIP PGRI TULUNGAGUNG, 2025)
SMP PGRI Rejotangan is one of the 7 schools in Rejotangan sub-district. Where PGRI Rejotangan Junior High School does not yet have a school website as a means of advertising or publication to provide information about the school completely, simply, quickly, and accurately. With the absence of school promotion media such as social media and the lack of publication of school information in the community, SMP PGRI Rejotangan has not been widely known by the public. This research aims to develop a feasible school website of SMP PGRI Rejotangan so that it can be utilized as a school information media. The type of research used is Research and Development (RnD) with the Personal Extreme Programming (PXP) model. Personal Extreme Programming (PXP) consists of 7 phases, namely: (1) Requirements, (2) Planning, (3) Iteration Initialization, (4) Design, (5) Implementation, (6) System Testing, (7) Retrospective. The results of the assessment from media expert I and media expert II can be stated that the product developed has reached very feasible criteria with a percentage achievement of 100% in the Compatibility aspect and 100% in the funtional suitability aspect. Meanwhile, the results of the assessment from the small group test can be stated that the product developed has reached the feasible criteria with a score of 97.5. Then the results of the assessment from the large group test obtained a score of 89.25 which was included in the Eligible criteria. Based on the results of the study, it is concluded that the PGRI Rejotangan Junior High School school website is suitable for use.Keywords: Personal Extreme Programming, Website